The use of widely targeted metabolite profiling to reveal the senescence changes in postharvest ‘Red Globe’ (Vitis vinifera) grape berries - Teng-fei XU; Xin YANG; Meng ZHANG; Shui-huan GUO; Wen-jing FU; Bi-jiang ZHOU; Yu-jia LIU; Hai-jun MA; Yu-lin FANG; Gang YANG; Jiang-fei MENG (Journal of Integrative Agriculture, 2022)
Changes in the metabolites of table grapes (Vitis vinifera) reportedly occur during postharvest senescence. The aim of this study was to determine the metabolomic differences in postharvest table grapes (‘Red Globe’) after being subjected to different senescence periods. To this end, we used widely targeted metabolomics based on ultra-performance liquid chromatography and tandem mass spectrometry. A total of 135 differential metabolites were identified. During postharvest senescence, the levels of most differential flavonoids (e.g., pelargonidin 3-O-glucoside, quercetin-3-O-glucoside, and cyanidin 3-O-glucoside) and L-aspartic acid decreased, while the levels of phenolic acids (e.g., trans-4-hydroxycinnamic acid methyl ester) and pantothenol increased. During early and late senescence, the levels of most differential lipids, especially LysoPC, as well as those of nucleotides and their derivatives, such as uridine, decreased and increased, respectively. Collectively, the findings of this study provide fundamental insights into the reasonable control of table grape fruit postharvest senescence and lay a solid foundation for further research.